Molecular Characterization of the Nsp2 and ORF5 (ORF5a) Genes of PRRSV Strains in Nine Provinces of China During 2016–2018 - Yin, Baishuang; Qi, Shanshan; Sha, Wanli; Qin, Hongyu; Liu, Liming; Yun, Jinyan; Zhu, Jinhai; Li, Guojiang; Sun, Dongbo (Frontiers in Veterinary Science, 2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) cause a highly contagious disease and brought huge economic losses to commercial pork production worldwide. PRRSV causes severe reproductive failure in sows and respiratory distress in piglets. To trace the evolution of PRRSV in some regions of China during 2016-2018, 112 suspected PRRS infection samples collected from 9 provinces in China during 2016-2018 were detected by RT-PCR, and analyzed by the Nsp2/ORF5 (ORF5a)-genes-phylogeny. Sequence analysis and recombination analysis were conducted on the Nsp2/ORF5 (ORF5a) genes of the identified strain in the study. The RT-PCR result shown that the positive rate of PRRSV was 50.89% (57/112). Phylogenetic analysis shown that the identified PRRSV strains were all NA genotype and belonged to lineage 1, 3 and 8. The Nsp2 gene of identified PRRSV strains shared nucleotide homologies of 53.0%~99.8%, and amino acid homologies of 46.8%~99.7%; The ORF5 gene of identified PRRSV strains shared nucleotide homologies of 82.4%~100%, and the amino acid homologies of 79.6%~100%. Sequence alignments identified a discontinuous 30-amino-acid deletion (positions 481 and 533-561) and a 131-amino-acid discontinuity deletion (positions 323-433, 481 and 533-551) in Nsp2 of PPRSV isolates; all identified strains in this study may be wild strains, and most identified strains may be highly virulent strains. The sequence alignment of ORF5 and ORF5a showed that were the mutation sites of GP5 mainly concentrated in the signal peptide and epitopes region, the mutation sites of ORF5a were concentrated in the transmembrane and the intramembrane region. The recombination analysis indicated that there may be multiple recombination regions in identified strains, and the recombination pattern was more complex. This study showed that the prevalent PRRSV strain in some regions of China was still HP-PRRSV, while NADC30 strain also occupied a certain proportion; different types of PRRSV strains showed different patterns and variation in China. This study suggested that the monitoring of PRRSV epidemics and genetic variation should be further strengthened.